Diagnosis of Growing Pain in Bangladeshi Pediatric Population - Saha, Santosh Kumar; Modak, Aditi; Chowdhury, Kamrunnahar; Uddin, Md Saleh; Ghosh, Dilip Kumar; Al-Mamun, Mohammad Abdullah (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Unexplained limb pain is a major diagnostic challenge. Parents become very much worried as their physician are not sure regarding accurate diagnosis of unexplained limb pain. Majority of the limb pain are due to Growing pain which can be diagnosed by using Standard Criteria. Objectives: The purpose of the present study was to see the clinical aspects of growing pain and to determine the causes of unexplained limb pain. Methodology: This study prospectively examined the presence of growing pain in a self reported population of children with limb pain of unexplained etiology attending National Center for Control of Rheumatic Fever and Heart Disease over the period of 6 months. Results: Total 57 children of 3-12 yrs of age were enrolled in this study and out of them 43(75.4%) were diagnosed as Growing Pain. Mean age of growing pain was 7.77(2.66). 19 children (44.2%) were male and 24 (55.8%) were female. Most frequent site of pain was calf (65.1%) and 95% cases pain occur at night. Growing Pain usually occur at slow growing period (86%) than rapid growing period (14%). Conclusion: Majority of unexplained limb pain are growing pain which is benign. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16251 J Shaheed Suhrawardy Med Coll, 2013;5(1):46-48